CISADON FOREST COFFEE ECOTOURISM MARKETING MODEL: FIELDS NOTES - Christomy, Tommy; Koesoemadinata, Fabianus Hiapianto; Ayu, Rahmatia; Wasono, Sunu; Datang, Frans Asisi (Journal of Environmental Science and Sustainable Development, 2022)
Cisadon is one of the villages that has coffee as one of the main sources of income for the local community. This research develops the marketing of Cisadon Forest Coffee through the ecotourism sector. Based on applied research, this research proves that the synergy between Kampung Atas and Kampung Bawah can improve the quality of coffee production in Kampung Cisadon. Cisadon Coffee production is developed by conducting sports tourism activities in a virtual race with the focus of Cisadon Coffee as a marketing icon. This research aims to increase community engagement and marketing of Cisadon Forest Coffee. By involving the indigenous people of Cisadon, this research indirectly also educates the community to understand that the coffee plant that grows in their area is a natural resource that can be utilized for their welfare. Thus, it is hoped that the understanding of coffee and its marketing techniques can be spread widely and evenly to realize the Cisadon tourism village.